(untitled) (مجلة البحوث الأكاديمية, 2021)
Five imported rice varieties (Herba, Abo bent, Al Hana, Uncle Benz and Al-Osra rice) were collected from private suppliers from 15 April to 25 Dec. 2019. Experiments were conducted in the labs of the High and Medium Center for Agricultural Sciences - Al Ghiran - Libya. The results were as follows: The highest average of length was recorded in Herba rice (6.2 mm), and the length ratio for width was in Herba and Uncle Benz (4.42, 4.00 mm) respectively, whiles the shortest varieties were Hana Rice (2.85 mm). The rice of the Al-Osra was short, where the average grain length was less than (5.2 mm) and the average grain width (2.25 mm) and the ratio of the width of this variety (6 mm), Which shows that the shape of a round and broad grain. The highest average weight of 500 grains was recorded in Uncle Benz rice (31.94 g), while Herba rice grains were of medium weight (22.09 g), while in Al-Hanaa rice, Al-Osra rice and Abo-bent rice (21.47, 21.10 and 18.56gm) respectively. Al-Osra rice recorded the highest average size (8 cm3), Uncle Benz rice recorded the highest density (6.38 g /cm3) among the varieties, followed by Al-Hana rice Herba rice (6.03, 3.15 g /cm3), Abo-bent rice, and Al-Osra rice (3.09, 2.63 g /cm3). All degrees of absorbency were varied, in the Al-Osra rice, Uncle Benz and Abo-bent rice (6.36, 5.25, 5.29 ml) respectively, whiles in Al Hanaa rice and Herba rice the degree of absorbency (4.64, 4.37 g). Herba rice has the highest volume increase (5 cm3) while the Uncle Benz rice has the lowest absorbency (2g). During the smell test conducted on the five varieties of rice under study, it was observed that Hana rice and Al-Osra rice resulted in a strong smell (strong) during cooking, while the smell of Herba rice was weak (Slight) and the rice was Uncle Benz was smell almost non-existent. The smell of Abo-bent rice was medium strength (Moderate). The results of the sensory evaluation showed that the rice varieties imported to the Libyan market are mostly good and characterized by good cooking properties. Their quality is graded in the following order: Uncle Benz, Al-Hana, Ab-obant, Herba and then Al-Osra rice.